Can performance-based incentives improve motivation of nurses and midwives in primary facilities in northern Ghana?: a quasi-experimental study - Aninanya, Gifty Apiung; Howard, Natasha; Williams, John E.; Apam, Benjamin; Prytherch, Helen; Loukanova, Svetla; Kamara, Eunice Karanja; Otupiri, Easmon (Global health action, 2016)
BackgroundLack of an adequate and well-performing health workforce has emerged as the biggest barrier to scaling up health services provision in sub-Saharan Africa. As the global community commits to the Sustainable Development Goals and universal health coverage, health workforce challenges are critical. In northern Ghana, performance-based incentives (PBIs) were introduced to improve health worker motivation and service quality.ObjectiveThe goal of this study was to determine the impact of PBIs on maternal health worker motivation in two districts in northern Ghana.DesignA quasi-experimental study design with pre- and post-intervention measurement was used. PBIs were implemented for 2 years in six health facilities in Kassena-Nankana District with six health facilities in Builsa District serving as comparison sites. Fifty pre- and post-intervention structured interviews and 66 post-intervention in-depth interviews were conducted with health workers. Motivation was assessed using constructs for job satisfaction, pride, intrinsic motivation, timelines/attendance, and organisational commitment. Quantitative data were analysed to determine changes in motivation between intervention and comparison facilities pre- and post-intervention using STATA™ version 13. Qualitative data were analysed thematically using NVivo 10 to explore possible reasons for quantitative findings.ResultsPBIs were associated with slightly improved maternal health worker motivation. Mean values for overall motivation between intervention and comparison health workers were 0.6 versus 0.7 at baseline and 0.8 versus 0.7 at end line, respectively. Differences at baseline and end line were 0.1 (p=0.40 and p=0.50 respectively), with an overall 0.01 difference in difference (p=0.90). Qualitative interviews indicated that PBIs encouraged health workers to work harder and be more punctual, increasing reported pride and job satisfaction.ConclusionsThe results contribute evidence on the effects of PBIs on motivational constructs among maternal health workers in primary care facilities in northern Ghana. PBIs appeared to improve motivation, but not dramatically, and the long-term and unintended effects of their introduction require additional study.
Gesehen am 18.08.2020